Implementation of the Independent Curriculum at SMA Negeri 1 Pontianak - Iwan Ramadhan; I. Imran; S. Suriyanisa (Inovasi Kurikulum, 2024)
The determination of the independent curriculum to become the national curriculum reflects the determination to adopt innovative approaches in teaching and adapt the curriculum to the changing needs of the times, as measured by assessment results, changes in student character, and competence in recent years. This research aims to determine the success of schools in adopting an independent curriculum. The research method used is a descriptive qualitative type to explore the curriculum implementation in the school environment and the intracurricular and co-curricular processes of SMA Negeri 1 Pontianak. Data collection techniques include observation of lessons and assessments, interviews with one sociology teacher and two teaching staff, and documentation. The research results on intracurricular and co-curricular intracurriculars regarding learning differentiation, and assessment were well conducted—measurable learning process activities from start to finish and assessment. Meanwhile, P5 activities are planned and carried out in detail to trigger students to develop their talents and potential in work and future challenges. Implementing differentiated learning and assessment and P5 went according to plan, and students at all levels achieved the P5 strengthening project. AbstrakPenetapan Kurikulum Merdeka, menjadi kurikulum nasional mencerminkan tekad untuk mengadopsi pendekatan inovatif dalam pengajaran, serta menyesuaikan kurikulum dengan kebutuhan zaman yang terus berubah, terukur dari hasil asesmen, perubahan karakter dan kompetensi peserta didik beberapa tahun ini. Penelitian ini bertujuan untuk mengetahui keberhasilan sekolah mengadopsi Kurikulum Merdeka. Metode penelitian yang digunakan ialah kualitatif jenis deskriptif untuk mendalami penerapan kurikulum di lingkungan sekolah dan proses intrakurikuler dan kokurikuler SMA Negeri 1 Pontianak. Teknik pengumpulan data melalui observasi pada pembelajaran dan asesmen, wawancara 1 guru Sosiologi dan 2 tenaga pendidik, serta dokumentasi. Hasil penelitian pada intrakurikuler dan kokurikuler, Intrakurikuler menyangkut diferensiasi pembelajaran dan asesmen terlaksana sangat baik. Terukur dari aktivitas proses pembelajaran dari awal hingga akhir dan asesmen. Sedangkan kegiatan P5, terencana dan terlaksana secara detail sehingga memicu peserta didik mengembangkan bakat dan potensi yang dimiliki dalam dunia kerja dan tantangan ke depannya. Penerapan pembelajaran serta asesmen berdiferensiasi dan P5 berjalan sesuai rancangan dan peserta didik semua jenjang mampu mencapai ketercapaian projek penguatan P5.Kata Kunci: Implementasi kurikulum; intrakuriler; kokurikuler; Kurikulum Merdeka